2012
DOI: 10.1007/s00167-012-2353-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the skeletal maturation of the distal attachment of the patellar tendon and physical features in preadolescent male football players

Abstract: Purpose: The aim of this study was to compare ultrasonography stages of the tibial tuberosity development and physical features. Methods Conclusions:Osgood-Schlatter pathogenesis reportedly involves increased quadriceps tightness with rapidly increasing femoral length during tibial tuberosity development. In this study, it was confirmed that quadriceps tightness increased, yet hamstring tightness decreased, suggesting that quadriceps tightness is not due to femoral length alone. Other factors, including muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 18 publications
1
38
0
1
Order By: Relevance
“…The apophysis is relatively weak and a common area of injury in sports participants. 1 Nakase et al 24 evaluated the stages of tibial tuberosity development and the physical features of 200 knees in 100 male football players aged 10 to 15 years using ultrasound. They found that quadriceps muscle tightness increased with skeletal maturation, while hamstring tightness did not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The apophysis is relatively weak and a common area of injury in sports participants. 1 Nakase et al 24 evaluated the stages of tibial tuberosity development and the physical features of 200 knees in 100 male football players aged 10 to 15 years using ultrasound. They found that quadriceps muscle tightness increased with skeletal maturation, while hamstring tightness did not.…”
Section: Discussionmentioning
confidence: 99%
“… 23 The following ultrasonographic findings were also required: fragmentation of the bone and irregularity of the ossification center in US ( Figure 2 ). 3 , 9 , 11 , 22 , 24 , 29 The physical findings were compared with the respective stages of tibial tuberosity development. Institutional review board approval for the study was provided by our institution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using ultrasonography, we developed a novel classification system of skeletal maturation of the distal attachment of the patellar tendon [10]. The sonolucent stage (stage S) is characterized by the presence of a large amount of apophyseal cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…Increased stiffness during the maximal rate of growth, has been linked to an increased injury risk in youth athletes [3]. Moreover, adolescents' cartilaginous structures like the articular surfaces, apophyses and physes, are in and of themselves more at risk for injury than mature bones as a result of growth [3,14,32]. It is supposed that after a period of growth, the cartilaginous structures are not immediately able to deal with a level of high stress, which could result in overuse syndromes like Osgood Schlatter disease, Morbus Sever disease [11].…”
mentioning
confidence: 99%